2017
DOI: 10.1186/s13256-016-1195-x
|View full text |Cite
|
Sign up to set email alerts
|

Twin pregnancy complicated by esophageal atresia, duodenal atresia, gastric perforation, and hypoplastic left heart structures in one twin: a case report and review of the literature

Abstract: BackgroundThe antenatal diagnosis of a combined esophageal atresia without tracheoesophageal fistula and duodenal atresia with or without gastric perforation is a rare occurrence. These diagnoses are difficult and can be suspected on ultrasound by nonspecific findings including a small stomach and polyhydramnios. Fetal magnetic resonance imaging adds significant anatomical detail and can aid in the diagnosis of these complicated cases. Upon an extensive literature review, there are no reports documenting these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In a recent literature review, Abou-Char et al found only two cases of visceral rupture. In their own case, gastric wall rupture was noted on fetal MRI in one fetus of a monochorionic-diamniotic twin pregnancy [ 4 ], and in Mitani et al , dilated structures noted on 26-weeks’ ultrasound were subsequently decompressed and associated with massive ascites 2 days later, suggesting enteric perforation [ 6 ]. Polyhydramnios was described in both cases and is an expected finding with in-utero gastrointestinal obstruction, making this case unique with intermittent and mildly elevated AFI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent literature review, Abou-Char et al found only two cases of visceral rupture. In their own case, gastric wall rupture was noted on fetal MRI in one fetus of a monochorionic-diamniotic twin pregnancy [ 4 ], and in Mitani et al , dilated structures noted on 26-weeks’ ultrasound were subsequently decompressed and associated with massive ascites 2 days later, suggesting enteric perforation [ 6 ]. Polyhydramnios was described in both cases and is an expected finding with in-utero gastrointestinal obstruction, making this case unique with intermittent and mildly elevated AFI.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrent duodenal and esophageal atresia is rare with few cases described in the literature [ 3–5 ]. Among those reported, specific prenatal imaging findings include the classic ‘double-bubble’ sign, gastric distention, polyhydramnios and a cystic thoracic structure consistent with a blind esophageal pouch [ 4 , 5 ]. When duodenal and esophageal atresia present together, the diagnosis can be difficult given the alterations in expected sonographic findings [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is the first study to address the comparison of the prenatal manifestation of EA/TEF between twins and singletons, and furthermore, between monochorionic and dichorionic pregnancies. The literature is mostly comprised of various case reports 27‐30 and a few epidemiologic studies with little reference to twins 31 . The only two existing articles on EA/TEF in twins address aspects other than prenatal diagnosis; One studied the concordance rate of EA/TEF in twins 32 and the other studied possible underlying mechanisms for the development of EA/TEF in twins 18 …”
Section: Discussionmentioning
confidence: 99%
“…EA is a rare anomaly with an incidence of 1–2 per 5000 births, which occurs more frequently in twins than in singletons 1 , while TTTS affects 15% of monochorionic pregnancies 2 . Despite the rapidly evolving advancement in fetal assessment in utero , prenatal diagnosis of EA is still suboptimal, with an estimated diagnostic rate of 50% 3 .…”
Section: Figurementioning
confidence: 99%